Prospects for cooling of marine organisms with the ice using chitosan and its polyelectrolyte complexes - Svetlana N. Maksimova; Svetlana Yu. Ponomarenko; Elena V. Surovtseva; Elena V. Fedoseeva; Denis V. Poleshchuk (Известия ТИНРО, 2016)
A new cooling medium for storage of fish and seafood is proposed - frozen water solution of polysaccharides of natural origin, as the natural biopolymer chitosan. Rational concentration of its solution for producing the chitosan ice is determined experimentally. Organoleptic, physical, and microbiological parameters of the ice prepared from solution of polyelectrolyte complexes of chitosan and its co-polymers are examined. Better results for cooling of marine raw materials are shown for the solution of polyelectrolyte complexes based on chitosan with sodium alginate and carboxymethyl cellulose. The chitosan-alginate ice is distinguished by higher density and homogeneous consistency within the temperature range from -5 to +5оC. Antiseptic microbiological activity of the chitosan-alginate ice is in 2.3 times higher as compared with the water ice and in 1.8 times higher than for the chitosan ice. High technological properties of the ice of polyelectrolyte complexes of chitosan with sodium alginate provide good prospects for its using in technology of cooling in fishery industry.